ANALISIS KEDISIPLINAN SISWA SMPN 10 SALATIGA MENYIKAPI PEMUTARAN LAGU INDONESIA RAYA SETIAP PUKUL 10.00 WIB - Katrine Ananda Sardiyosa; Wildan Imaduddin; Muhammad Sirril Wafa; Tanaya Elghifara Syah Rizal; Noor Malihah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Student discipline in responding to the playing of the Indonesian national anthem is an important part character of nationalism and respect for national symbols in the school environment. However, in practice, there are still variations in student responses, ranging from punctuality in standing, awareness of following the rules, to respectful behavior while the song is playing. This study aims to analyze the discipline of students at SMP 10 Salatiga in responding to the playing of the Indonesia Raya every day at 10:00 a.m. and to identify the factors that influence this behavior. The study uses a descriptive qualitative approach with observation, interviews, and documentation techniques. Data was obtained from teachers, students, and school officials directly involved in the implementation of this discipline program. The results showed that most students demonstrated disciplined behavior, such as stopping their activities, standing at attention, and following the teacher's instructions, in line with the finding that routine school activities can strengthen moral character and discipline. However, several obstacles were found, such as a lack of supervision at certain points, a low understanding of the meaning of the activities, and differences in individual awareness. In conclusion, student discipline is influenced by the consistency of school rules, teacher role models, and student understanding of the value of nationalism. Strengthening socialization and routine monitoring are necessary to maintain the sustainability of a culture of discipline in schools. ABSTRAK Kedisiplinan siswa dalam menyikapi pemutaran Lagu Indonesia Raya merupakan bagian penting dari pembentukan karakter nasionalisme dan penghargaan terhadap simbol negara di lingkungan sekolah. Namun, dalam praktiknya masih ditemukan variasi respons siswa, mulai dari ketepatan waktu berdiri, kesadaran mengikuti aturan, hingga sikap menghormati selama lagu diputar. Pengabdian ini bertujuan untuk menganalisis bentuk kedisiplinan siswa SMP 10 Salatiga dalam merespons pemutaran Lagu Indonesia Raya setiap pukul 10.00 WIB serta mengidentifikasi faktor yang memengaruhi perilaku tersebut. Pengabdian menggunakan pendekatan kualitatif deskriptif dengan teknik observasi, wawancara, dan dokumentasi. Data diperoleh dari guru, siswa, dan pihak sekolah yang terlibat langsung dalam pelaksanaan program kedisiplinan ini. Hasil pengabdian menunjukkan bahwa sebagian besar siswa telah menunjukkan sikap disiplin seperti berhenti beraktivitas, berdiri tegap, dan mengikuti instruksi guru, sejalan dengan temuan bahwa kegiatan rutin sekolah dapat memperkuat karakter moral dan kedisiplinan. Namun, beberapa kendala ditemukan, seperti kurangnya pengawasan di titik tertentu, rendahnya pemahaman tentang makna kegiatan, serta perbedaan kesadaran individu. Kesimpulannya, kedisiplinan siswa dipengaruhi oleh konsistensi aturan sekolah, keteladanan guru, dan pemahaman siswa terhadap nilai nasionalisme. Penguatan sosialisasi dan monitoring rutin diperlukan untuk menjaga keberlanjutan budaya disiplin di sekolah.